Folk Healing Practices and Christian Faith Among Selected Residents of Ternate, Cavite, Philippines - Astorga, John Mark (CV. Rayyan Dwi Bharata, 2025)
This paper aims to know the experiences of the selected Christian residents of San Juan, Ternate, Cavite in consulting folk healers and to examine the awareness of the participants in their church’s stance on folk healing practices. Folk healing was a huge part of Filipino culture long before the Colonial period. Folk healers or also known as Albularyos serve as spiritual and medicinal figures in the Philippines, especially in the provinces where there is poverty. This paper uses a Qualitative method through structured interviews to answer the research questions. Using Purposive sampling technique, 8 participants from Ternate, Cavite who are devoted Christians were carefully selected to be the perfect respondents of this study. Interestingly, all of the respondents are not informed about the church’s stance on folk healing, most of them are regular church attendees and also visit folk healers regularly. This paper offers recommendations to help the church disseminate her teachings without discrimination.